1974
DOI: 10.1113/jphysiol.1974.sp010497
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the production of sodium depletion by peritoneal dialysis with 5% glucose on the volume and composition of the extracellular fluid of dogs

Abstract: SUMMARY1. The volumes and compositions of the extracellular and peritoneal fluids were monitored in functionally nephrectomized dogs during a period of 4 hr of peritoneal dialysis with 5 % glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The significant ultrafiltration in the NS group despite the initial osmolality of this solution being slightly hypo-osmotic is in agreement with previous studies (15,26,27). As also shown in a previous study (15), we found that the dialysate osmolality in this solution increased to higher than plasma level after 15 minutes of dwell.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 93%
“…The significant ultrafiltration in the NS group despite the initial osmolality of this solution being slightly hypo-osmotic is in agreement with previous studies (15,26,27). As also shown in a previous study (15), we found that the dialysate osmolality in this solution increased to higher than plasma level after 15 minutes of dwell.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 93%